Quantum chemical quantitative structure activity studies of anticancer activity of Aldohexose chloroethylnitrosourea Analogs - Noorbatcha, Ibrahim Ali; Syed Osman Idid, Syed Zahir Idid; Eissa, Maimonah (2010)
Quantitative structure activity relationship involving 18 aldohexose chloroethylnitrosourea compounds having anticancer activity against Ip-Implanted Murine L1210 Lymphoid Leukemia, is investigated using semi-empirical quantum chemical AM1 methods.